Iodine test to detect physical damage in chickpea seeds - Jose de Oliveira Cruz; Luís Carlos de Carvalho Júnior; Ricardo Carmona; Jônatas Barros dos Santos; Isabella Fuckner Artiaga (Revista Ciência Agronômica, 2025)
ABSTRACT The chickpea (Cicer arietinum L.) is the third most cultivated legume in the world and the second most consumed. One of the main problems in producing seed of this species is the mechanical damage generated when harvesting or during post-harvest. With the aim of developing a protocol for rapid iodine testing, the aim of this study was to determine the most suitable exposure time for chickpea seeds in iodine solution, and the most appropriate concentration for staining naturally or artificially damaged seeds. Concentrations of 5%, 10% and 15% (commercial product containing 2% iodine) were tested on both intact and artificially damaged seeds for an immersion time of 2.5, 5.0, 10.0, 15.0 and 20.0 minutes. The correlation between the colour and the physical and physiological properties of ten seed batches exposed to 10% iodine for 10 and 15 minutes was also evaluated. The data were submitted to univariate and multivariate analysis. The iodine test, at a concentration of 10% of the commercial product (iodine concentration of 2%) for 15 minutes, is effective in evaluating the level of mechanical damage in chickpea seeds, due to the negative correlation between the colour of the seeds in the test and the physical and physiological qualities of the seeds.